Y-3*-2=0

Simple and best practice solution for Y-3*-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-3*-2=0 equation:


Simplifying
Y + -3 * -2 = 0

Multiply -3 * -2
Y + 6 = 0

Reorder the terms:
6 + Y = 0

Solving
6 + Y = 0

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + Y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + Y = 0 + -6
Y = 0 + -6

Combine like terms: 0 + -6 = -6
Y = -6

Simplifying
Y = -6

See similar equations:

| 6u^2-19u+10=0 | | a(3a-1)=4 | | (x-5)(x+2)=18 | | 7-3(5-5x)=0 | | 7c^2-91c+210=0 | | 6x^2-12=-x | | (10x-8)=4x+28 | | 2x+9y=5 | | 3x^2=-21x | | x^2+x=-5x+16 | | 2-4(9x+3)=7 | | 0.4x+0.4=0.8x-0.4 | | x^2+16x=21x-6 | | 2*0+y=4 | | 9x^2-18x=-5 | | 5x^2+18x=-x+4 | | 2(-8x-5)=9 | | x^2+15=10x-6 | | 5.5x^2+x-1.1=4x(3-x) | | x^2-5x=-4x+56 | | (b^3-2b^2+b)-(b^2+3b-1)=0 | | (-8x-5)=9 | | 3(2x+9)=-27+48 | | 5x^2+5x=14x+2 | | (b^2-2b^2+b)-(b^2+3b-1)= | | x^2+35x+300=0 | | 8x^2-34x=-21 | | 30x^2=42x | | 1/3(y-6)=4y-2/5(2-y) | | y-(-1)= | | y-(-4)= | | x+6=y |

Equations solver categories